Implementation Of Project Based Learning Through Making A Video As The Alternative Assignment and Its Effect Toward Motivation and Comprehension of Students in SMA MADANIA BOGOR - Yuvita Oktarisa (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2015)
This research originated from the interviewing between the researcher as a physics teacher to some students about Physics assignments. Based on the interview, student felt so bored in doing their assignment and have no motivation in finishing it. Because there is no motivation in doing the assignment therefore the understanding of the students could not be increasing. Based on Curtis (2009:1) that motivation of the students could be increased by implementing  Project Based learning (PBL). This research tried to see the influence of PBL toward the motivation and the understanding of the students. In this assignment students are asked to making a video about the application of Newton’s law of Motion in daily Life. From this video students analyzing why do the video can categorize as the application of Newton’s Law of Motion in daily Life. In making the video as the project, students are guided by the rubric, the timeline and also the goal of the project. Students have to finish their project in fifteen days, and teacher scored their project based on two criteria: the contents and presentation. Ten best video would be shown in front of the whole students in an event in the school. To see the understanding and the motivation of the students after finishing the project, the teacher gave the test and also the questionnaire about the project and their comprehension of Newton’s Law of Motion. According to the questionnaire we can see that more than 60% of the students agree that the project can increase their motivation and also their understanding. The increasing of students comprehension can be seen from the test that given to students. From this research we can inferred that project base learning can stimulus student’s motivation and also the understanding.